JIHAD AS A PERVERSE CONCEPT OF MODERN ISLAMIC FUNDAMENTALISTS - Zelenkov, Mikhail; Brushkova, Lyudmila; Denikin, Anatoly; Denikina, Zoya; Korablin, Yuriy (Revista Inclusiones, 2020)
The object of this study is jihad, as one of the pillars of the world religion of Islam. The subject of the study is the concept of jihad in the interpretation of modern Islamic fundamentalists and adherents of the traditional Muslim faith. The authors set a goal based on the results of the analysis of approaches to the interpretation of jihad in the theological and scientific literature to identify the adequacy of its interpretation by representatives of traditional and fundamentalist Islam, to assess its impact on the activities of modern Islamic terrorist organizations.